Aplicabildade das ferramentas da produção enxuta em operações de serviços: uma análise segundo as dimensões de volume e variedade - Brito, Taíse Câmara (2015)
In spite of its origins in the manufacturing sector, lean production has been recognized in service organizations as a management model which is able to assist managers to minimize or eliminate their waste, reducing costs and increasing the efficiency of an organization. Academic literature provides empirical evidence of the application of lean tools in the service sector, such as in hospitality, call centers, insurance companies, and especially in hospitals. Although it is possible to find practical applications, it cannot be stated that all processes have the same degree of applicability of lean production. Therefore, this dissertation investigated the applicability of lean production in different types of service processes in order to understand the implications of volume and variety dimensions to the implementation of a lean system. Thus, it was initially performed a literature survey to identify the current state of the research on the application of lean production in the service processes. In the field research, six different service processes were selected and a case study was conducted for each: technology consulting, medical consultation, car sales, car maintenance and repair, road bus service and fast-food. The first step was to identify the position of each of the processes in the volume and variety matrix. Then, the influence of each dimension on the applicability of lean tools was verified, disclosing positive influences, negative influences or even demonstrating those dimensions that did not have any influence on applicability. It was observed that there are characteristics that act as facilitators and other as barriers to the applicability of lean service. Although it is possible to isolate facilitators and barriers, it can also be concluded that the applicability of lean production in service operations depends on the existence of various process dimensions acting together.